Role-playing group counseling in character-strengthening education in high school students - Bakhrudin All Habsy (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2022)
Purpose - This research aims to measure the effectiveness of counseling groups using the technique of role-playing in the framework of character-strengthening education in high school students.Method - research type used is quantitative with a quasi-experimental design. This study involves two object groups: experiment group and control group. These groups are set through a random method.Result - Counseling group with role-playing technique is proven to be effective in strengthening the character of the participants. This can be seen from the paired sample T-test where the significance score was 0.000 (p0.05). Thus, strengthening the character through a role-playing technique that includes the score of religious, nationalist, independent, mutual cooperation, and integrity shows significant changes in the results. _Implications - This study the impact on the development of service guidance and counseling in high school as an effort to build character’s participants teach to fit with the score of character education.Originality - This research is strengthening character education through counseling group service with a role-playing technique for high school students.***Purpose - Penelitian ini bertujuan untuk mengukur efektifitas konseling kelompok menggunakan teknik role playing dalam rangka penguatan pendidikan karakter pada siswa Sekolah Menengah Atas (SMA).Method - Jenis penelitian yang digunakan adalah kuantitatif dengan desain quasi eksperimen. Penelitian ini melibatkan dua objek kelompok yakni kelompok eksperimen dan kelompok kontrol. Penentuan kelompok ditetapkan melalui metode acak.Result - Konseling kelompok dengan teknik role playing terbukti efektif dalam penguatan karakter peserta didik. Hal ini terlihat dari uji paired sample T-test dimana nilai signifikansi menunjukkan angka 0,000 (p0,05). Dengan demikian, penguatan karakter melalui teknik role playing yang meliputi nilai religius, nasionalis, mandiri, gotong-royong dan integritas menunjukkan hasil perubahan yang signifikan.Implications - Kajian ini berdampak pada pengembangan layanan bimbingan dan konseling di SMA sebagai upaya penanaman karakter peserta didik agar sesuai dengan nilai pendidikan karakter.Originality - Penelitian ini merupakan kajian penguatan pendidikan karakter melalui layanan konseling kelompok dengan teknik role playing pada siswa SMA.